Implementation of the Community Based Tourism (CBT) Concept in the Development of Sumberdem Tourism Village - Budi Wahono; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardhana (JURNAL RISET MANAJEMEN (JURMA), 2024)
The Sumberdem Tourism Village is located in the Wonosari District of Malang Regency. It is situated on the slopes of Mount Kawi, recognised as a site with potential to develop into a tourist destination. The local administration endorses the establishment of a Tourism Village and is optimistic that it will offer remarkable opportunities for community development and economic enhancement. This study identifies the characteristics that facilitate the transition of Sumberdem Village into a tourist destination. The researcher aims to analyse the evolution of Sumberdem Tourism Village. The author employed interviews and documentation methods as data gathering strategies in this research. Interviews were executed systematically, utilising prearranged questions for the participants. The researcher employed SWOT and PEST analytical approaches to enhance the data. Subsequently, researchers employed source triangulation methods to assess the data's validity. This research culminated in a tourism village development strategy that identifies possibilities and risks from both internal and external sources. This research analysis examines the potential effects and future prospects of the study. Sumberdem Village possesses numerous potentials, including coffee plantations, bamboo forests, water springs, and goat farms, alongside social and cultural aspects such as community arts and traditions. The findings indicate that Sumberdem Tourism Village needs assistance from multiple stakeholders to formalise its status as a legitimate tourist destination and to enhance training and development for Pokdarwis and the local population.